Structural and functional swapping of amyloidogenic and antimicrobial peptides: Redefining the role of amyloidogenic propensity in disease and host defense. (4th November 2021) - Yadav, Jay Kant
Abstract : Peptides constitute an essential component of all organisms' protein homeostasis ranging from bacteria, plants, and animals. They have organically been evolved to perform a wide range of essential functions, including their role as neurotransmitters, antimicrobial peptides (AMPs), and hormones. AMPs are short peptides synthesized by almost all organisms, implicated in guarding the host from various microbial infections. Their inherent ability to differentiate the target microbes from the host confers them excellent prospects in fighting against microbial infections and affirming their robust therapeutic potential against numerous drug‐resistant microbes. Amyloidogenic peptides (AMYs) represent another class of short peptides armed with inherent aggregation propensity and form fibrillar aggregates rich in cross β‐sheet structure. They are often involved in various degenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), and type‐2 diabetes. Although these two distinct classes of peptides (i.e., AMPs and AMYs) appear to be functionally divergent, recent studies suggest that they possess a significant degree of structural and functional reciprocity. Consistent with this, many AMPs display amphiphilic nature, and hence, they can facilitate membrane remodeling processes, such as pore formation and fusion, similar to AMYs. The mounting evidence suggests the inherent ability of AMPs to self‐assemble to form amyloid‐like structures. On the other hand, the demonstration of antimicrobial properties of AMYs in their monomeric conformation provides a hint about the existence of an evolutionary linkage between these two classes of peptides. The congregation of specific amino acids to form aggregation‐prone regions in a protein/peptide might have served as an evolutionary reservoir from which AMPs and AMYs were consecutively evolved. The current article reviews the fundamental features of the AMPs, AMYs, and their inter‐relatedness and emerging paradigm for their inter‐conversion. Abstract : Antimicrobial peptides (AMPs) and amyloid‐forming peptides (AMYs) represent two essential categories of biomolecules with their distinct structural and functional identities. Recent investigations in this field outline the pieces of evidence for structural and functional swapping among each other. The review summarizes the underlying fundamental mechanisms responsible for their mutualistic swapping among each other and provides a window of opportunity for developing novel AMPs/AMPYs with diverse potential applications.